Prediking en geloofservaring: Gesprek oor die teologiese gehalte van die preek - Pieterse, Hendrik J. C. (Hervormde teologiese studies, 1989)
Preaching and the experience of faith. Discussion on the theological character of the sermon Empirical studies show that the community of believers in the churches of the Reformation expects an encounter with God through preaching. These studies also show that this expectation is not always met. The problem that concerns us here is whether a sermon based on modern exegesis can communicate God in such away that an encounter facilitating faith is possible. An attempt is made to find a solution by reflecting on a specific presupposition in the hermeneutical process when preparing a sermon.